71 Medilead: leadership for junior doctors, by junior doctors. (31st October 2017) - Chachlani, Menka; Harris, Rhydian; Jones, David; Dwyer, Lesley; Hare, Sarah
Abstract : Background: The Faculty of Medical Leadership and Management, the NHS Leadership Framework and most Royal Colleges recognise that Junior Doctors need to be trained with appropriate Quality Improvement and Leadership skills. The practicalities of developing a robust programme for this, however, remain difficult. Whilst limited leadership roles do exist, most Junior Doctors have limited experience in medical leadership and change management prior to completion of training. We wanted to address this training need by providing an engaging leadership programme to Junior Doctors, whilst in clinical roles. Aims: MediLead is a bespoke scheme for quality improvement and leadership. We aim to harness Junior Doctors' enthusiasm in their work and demonstrate positive effects of change management. Methods: A series of monthly seminars, workshops and practical sessions throughout a training year. These sessions were led by influential individuals both from a clinical and non-clinical background. Executive-level events were offered to delegates. Results: MediLead delegates have delivered over 30 Quality Improvement projects in 2 years. Projects included improving patient hydration; an app providing hospital guidelines for managing common emergencies; generating additional revenue from clinical coding, and setting up a buddying system for Junior Doctors. Follow up audits have demonstrated improvements in patient safety and outcomes. Outcomes from MediLead projects contributed to Medway NHS Trust exiting special measures in 2016. MediLead delegates presented at the patient Safety Congress Awards 2017, and in 2016 one QI project was used by NICE as an example of outstanding QI methodology. Conclusions: MediLead provides a foundation in engaging, enabling and empowering Junior Doctors in leadership throughout our Trust alongside clinical commitments. With further Trust encouragement, we plan to continue to empower all Junior Doctors to ultimately improve patient care.